(untitled) (Nordic Journal of African Studies, 2009)
War propaganda during the Second World War in colonial Nigeria, preceded by local protestations of loyalty and support of Britain, was inappropriately focused, discredited as lies, and unable either to stem the movement towards self-government or to sustain Nigerians’ acceptance of the colonial state as a viable framework for the achievement of an enduring welfare and political freedom. Relying on archival sources previously ignored by scholars, the paper challenges the conventional wisdom that war propaganda in Africa profoundly affected the elite, who appropriated British propaganda as a weapon to undermine the colonial state. It argues that the effect of war propaganda was practically nil, in eroding confidence in local role models, newspapers and other sources of propaganda which reflected local realities and concerns. In short, at the end of the war, the colonial regime abandoned this failed propaganda strategy in search of a robust no-bones-about-it abrasive propaganda approach.